Platelet-Specific p38α Deficiency Improved Cardiac Function After Myocardial Infarction in Mice. Issue 12 (December 2017) - Shi, Panlai; Zhang, Lin; Zhang, Mingliang; Yang, Wenlong; Wang, Kemin; Zhang, Junfeng; Otsu, Kinya; Huang, Gonghua; Fan, Xuemei; Liu, Junling
Abstract : Objective—: MAPKs (mitogen-activated protein kinases), especially p38, play detrimental roles in cardiac diseases and cardiac remodeling post-myocardial infarction. However, the activation and function of MAPKs in coronary thrombosis in vivo and its relationship with clinical outcomes remain poorly understood. Approach and Results—: Here, we showed that p38α was the major isoform expressed in human and mouse platelets. Platelet-specific p38α-deficient mice presented impaired thrombosis and hemostasis but had improved cardiac function, reduced infarct size, decreased inflammatory response, and microthrombus in a left anterior descending artery ligation model. Signaling analysis revealed that p38 activation was one of the earliest events in platelets after treatment with receptor agonists or reactive oxygen species. p38α/MAPK-activated protein kinase 2/heat shock protein 27 and p38α/cytosolic phospholipases A2 were the major pathways regulating receptor-mediated or hydrogen peroxide-induced platelet activation in an ischemic environment. Moreover, the distinct roles of ERK1/2 (extracellular signal–regulated kinase) in receptor- or reactive oxygen species-induced p38-mediated platelet activation reflected the complicated synergistic relationships among MAPKs. Analysis of clinical samples revealed that MAPKs were highly phosphorylated in platelets from preoperative patients with ST-segment–elevation myocardial infarction, and increased phosphorylation of p38 was associated with no-reflow outcomes. Conclusions—: We conclude that p38α serves as a critical regulator of platelet activation and potential indicator of highly thrombotic lesions and no-reflow, and inhibition of platelet p38α may improve clinical outcomes in subjects with ST-segment–elevation myocardial infarction. Abstract : Supplemental Digital Content is available in the text.